Membrane Stabilitiy and Removal of Cobalt from Waste Solution Using Liquid Emulsion Membrane - Mohamed, Y. T.; Hussin, L.M. S.; Gad, H.M. H.; Daifullah, A.A. M.; Abo-El-Enein, S. A. (Journal of Membrane and Separation Technology, 2013)
A Liquid Emulsion Mmenrane (LEM) containing Cyanex 301 as a carrier and Span 80 as a surfactant was used for the extraction of Co-(II) from nitric acid solution. Various diluents were tested and cyclohexane was found the most effective diluent in the cobalt extraction. The effect of different factors affecting the permeation of cobalt through LEM (e.g pH of the extrenal phase, type and concentration of stripping internal phase, the equilibrium time, and Cyanex 301 conentration) were investigated. The effects of surfactant types and cocentrations on the stbility of LEM were also studied. It was found that the optimum conditions for cobalt extraction using 8% Cyanex 301 were as follows; 3M HCl as an internal phase, 4% span 80 as a surfactant and by using the best conditions 10 ml of prepared LEM can extract about 96.86% of 1 gm/l of cobalt in Nitric acid solution after 5 min. in the reactor tank.